Commendable Attitudes And Deeds As A Condition For Commutation Of The Death Penalty Perspective Q.S. Al-Maidah (5): 33-34 - Suci Hidayati Malau; Noor Azizah (PALAR | PAKUAN LAW REVIEW, 2026)
Article 100 of Law Number 1 of 2023 concerning the Criminal Code makes "commendable attitudes and deeds" a condition for commutation of the death penalty. However, these provisions do not provide clear parameters so that they have the potential to cause legal uncertainty and subjectivity in their assessment. This study aims to analyze the criteria of "commendable attitudes and deeds" as a requirement for the commutation of the death penalty in Indonesian criminal law and examine it based on the perspective of Q.S. Al-Maidah (5): 33–34. This research is a normative legal research with legislative, conceptual, and comparative approaches. Data were obtained through literature studies and analyzed qualitatively using interpretive and comparative methods. The results of the study show that Article 100 of the Criminal Code has not provided normative indicators regarding "commendable attitudes and deeds", thus opening up a wide range of interpretations. Meanwhile, Q.S. Al-Maidah (5): 33–34 through the concept of repentance provides more concrete parameters, namely real behavior change, cessation of criminal acts, confession of guilt, self-improvement, and fulfillment of the rights of victims. The concept of repentance in Q.S. Al-Maidah (5): 33–34 can be a normative perspective in formulating the parameters of "commendable attitudes and deeds" as a condition for the commutation of the death penalty.   Keywords: Death Penalty Commutation; Commendable Attitudes and Deeds; Q.S. al-Maidah (5): 33-34.